2016
DOI: 10.5604/20831862.1196510
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SCGB1C1 gene as a potential marker of susceptibility to upper respiratory tract infections in elite athletes – a pilot study

Abstract: High levels of exercise in athletes result in temporary immunosuppression, which could increase the susceptibility to upper respiratory tract infections. Understanding of immunological mechanisms responsible for this phenomenon could enable optimization of training schemes for elite athletes and avoidance of infection-related episodes of absence during sports championships. The aim of this study was to detect genes that may be responsible for modulation of individual susceptibility to infections. The blood and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…As mentioned above, fewer studies have focused on other SCGBs, but it has been shown that SCGB1C1 is also important for the protection of lung epithelial cells: It recognizes and removes pathogens from the airway mucosa 46 . It also seems to be involved in the development of a common cold 1,46,47 . Elite athletes appear to be more prone to upper airway infections and expression of serum SCGB1C1.…”
Section: Secretoglobins In Diseases Of the Upper And Lower Airwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, fewer studies have focused on other SCGBs, but it has been shown that SCGB1C1 is also important for the protection of lung epithelial cells: It recognizes and removes pathogens from the airway mucosa 46 . It also seems to be involved in the development of a common cold 1,46,47 . Elite athletes appear to be more prone to upper airway infections and expression of serum SCGB1C1.…”
Section: Secretoglobins In Diseases Of the Upper And Lower Airwaysmentioning
confidence: 99%
“…Elite athletes appear to be more prone to upper airway infections and expression of serum SCGB1C1. Thus, SCGB1C1 could serve as a parameter for susceptibility to respiratory infections, as described for SCGB1A1 43,47 …”
Section: Secretoglobins In Diseases Of the Upper And Lower Airwaysmentioning
confidence: 99%
“…Nevertheless, they may both lack downregulation through IFN-γ ( Supplementary Table S1 ). The SCGB1C1 may be regarded as part of the host response protection against the common cold, as reviewed by Orysiak et al [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this was downregulated in athletes with a below-mean IgA and deletion involved in susceptibility to psoriasis [ 25 , 26 ]. The late cornified envelope 3D gene LCE3D was distinctly downregulated in CRSsNP.…”
Section: Discussionmentioning
confidence: 99%
“…Igfbp6 is also associated with cell growth and fibroblast proliferation in asthmatics [ 47 ]. Scgb1c1 is mainly expressed in the human respiratory tract mucosa and is downregulated by IFN-r and upregulated by IL-4 and IL-13 [ 48 50 ]. Scgb1c1 also plays an important role in protecting lung epithelial cells by recognizing and eliminating pathogenic microorganisms in the mucous membranes [ 48 ].…”
Section: Discussionmentioning
confidence: 99%